Authentic STEM research, practices of science, and interest development in an informal science education program - Bobby Habig; Preeti Gupta (International Journal of STEM Education, 2021)
Abstract Background Two critical challenges in science education are how to engage students in the practices of science and how to develop and sustain interest. The goal of this study was to examine the extent to which high school youth, the majority of whom are members of racial and ethnic groups historically underrepresented in STEM, learn the skills and practices of science and in turn develop interest in conducting scientific research as part of their career pursuits. To accomplish this goal, we applied Hidi and Renninger’s well-tested theoretical framework for studying interest development in the context of a museum-based, informal science education (ISE) program. We used a mixed methods approach, incorporating both survey and interview data, to address three research questions: (1) As youth engage in authentic science research, do they develop perceived competence in mastering the skills and practices of science? (2) Do participants increase, maintain, or decrease interest in science research as a result of this experience? (3) How does participation in scientific practices manifest in non-program contexts? Results Our study yielded three main results. First, we found that participants developed competence in mastering several of the skills and practices of science. Strikingly, there was significant improvement in self-reported level of competency for 15 specific research skills. Second, we found that participants maintained their interest in scientific research over time. Our post-survey results revealed that one hundred percent of students were either excited about or expressed deep interest in scientific research. Based on a Phases of Interest Development Rubric developed for this study, most participants exhibited emerging individual interest. Finally, participants exhibited significant increases in the frequency in which they engaged in scientific practices outside of the program. Conclusions Our findings suggest that participation in authentic research in an ISE context affords youth critical opportunities for gaining mastery of several of the skills and practices of science, which in turn reinforces, and in some cases increases participants’ interest in scientific research beyond the span of the program.